Data Network for India - Srinivasan, R. (Journal of Information and Knowledge, 1987)
The development of telecommunications network has been traced, contributions of these developments to socio-economic development has also been discussed. The valve satellite technology in the spread of telecommunication facility has been pointed out. The computer-communication network development in India has been traced. The need for nation-wide data network for quick transfer of information and the infrastructural facility needed for the same are presented. The application of data network in integrating varieties of resources and activities such as water, electricity, oil, transport, health and network, discusses. Configurations of data transfer network, the nodes in transfer network and other modular aspects have been discussed. Illustrations of data transfer network model is given.